Development of anti-CD47 single-chain variable fragment targeted magnetic nanoparticles for treatment of human bladder cancer. (March 2017) - Rezaei, Gashin; Habibi-Anbouhi, Mahdi; Mahmoudi, Morteza; Azadmanesh, Kayhan; Moradi-Kalbolandi, Shima; Behdani, Mahdi; Ghazizadeh, Leila; Abolhassani, Mohsen; Shokrgozar, Mohammad Ali
Aim: To develop a novel anti-CD47 single-chain variable fragment (scFv) functionalized magnetic nanoparticles (MNPs) for targeting bladder cell lines and its applicability in thermotherapy.Material & methods: An immunized murine antibody phage display library was constructed and screened to isolate anti-CD47 binders. A scFv was selected and conjugated to MNPs which was then utilized to discriminate CD47 + bladder cells along with assessing its efficacy in thermotherapy.Results: An scFv with high affinity to bladder cells was efficiently conjugated to MNPs. Following a hyperthermia treatment, the function of scFv–MNP conjugates led to a considerable reduction in cell viability.Conclusion: The anti-CD47 scFv–MNP conjugate was an effective cancer cell thermotherapy tool that might pave the way for development of bionano-based targeting techniques in both early detection and treatment of cancer.